Status of sperm-born oocyte activating factors (PAWP, PLCζ) and sperm chromatin in uncapacitated, capacitated and acrosome-reacted conditions. (3rd April 2017) - Tavalaee, Marziyeh; Parivar, Kazem; Shahverdi, Abdol-Hossein; Ghaedi, Kamran; Nasr-Esfahani, Mohammad Hossein
Abstract: The aim of this study was to investigate the value of sperm factors PAWP and PLCζ involved in oocyte activation and sperm chromatin status, as indicators of sperm quality during uncapacitated, capacitated and acrosome-reacted conditions. Semen samples collected from 10 normozoospermic men and sperm factors PAWP, PLCζ, protamine deficiency and DNA fragmentation evaluated in fresh samples, processed sample by DGC (density gradient centrifugation), capacitated and acrosome reacted sperm, using immunofluorescence and flow cytometry. The status of capacitation and the acrosome reaction were confirmed by tyrosine kinase phosphorylation and CD46 markers, respectively. The proportion of sperm-expressing weak or zero levels of PLCζ and PAWP were significantly reduced after DGC processing. There were no significant differences among processed DGC, capacitated and acrosome-reacted samples. The proportions of DNA fragmented and protamine-deficient spermatozoa were decreased after DGC and maintained during capacitation and the acrosome reaction. DGC processing, therefore, improved the quality of sperm in terms of chromatin and DNA integrity, and removed sperm which may have had a lower potential to induce oocyte activation and undergo capacitation and the acrosome reaction.